Recht und Wirtschaft in Stadt und Land : Neunter Rechtshistorikertag im Ostseeraum : 16.-20. Mai 2018 in Tallinn, Sagadi und Tartu, Estland = Law and economics in urban and rural environment : 9th Conference in Legal History in the Baltic Sea Area : 16-20 May 2018 in Tallinn, Sagadi and Tartu, Estonia - Rechtshistorikertag im Ostseeraum 2018 (2020)
Der Sammelband dokumentiert ausgewählte Vorträge des Neunten Rechtshistorikertages im Ostseeraum vom Mai 2018 in Estland. Die Beiträge decken unter dem Generalthema «Recht und Wirtschaft in Stadt und Land» die gesamte Spannbreite der Rechtsgeschichte des Ostseeraumes sowie der Forschungsinteressen der Rechtshistorikerinnen und Rechtshistoriker der Anrainerstaaten ab. The anthology documents selected presentations of the 9th Conference in Legal History in the Baltic Sea Area from May 2018 in Estonia. Under the general theme «Law and Economics in Urban and Rural Areas», the contributions cover the entire range of the legal history of this region as well as the research interests of legal historians in the neighbouring states.